The Influence of Financial Technology on Saving Behavior Through Self-Control as a Mediator in Generation Z - Widyaningrum, Indah; Paradita, Gusti Enggar; Pratiwi, Permata Dian (Dinasti Publisher, 2024)
This research aims to test and analyze the influence of financial technology on saving behavior with self-control as a mediating variable in Generation Z. Developments in financial technology influence the way Generation Z manages their finances. This research uses a quantitative descriptive method by collecting data through online questionnaires and using 400 Generation Z respondents in West Java. Structural Equation Modeling Partial Least Squares (SEM-PLS) was used as an analysis method in this research. The research results show that financial technology has a positive effect on saving behavior, financial technology has a positive effect on self-control, self-control has a positive effect on saving behavior, and self-control has a positive effect in the mediation of financial technology on saving behavior.